Mexico : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that the economic slowdown in the United States triggered a sharp weakening in Mexican economic activity in 2001 from the rapid pace in the preceding year. There was also a marked deceleration in domestic demand growth, as disposable income was adversely affected by a contraction in employment and confidence sagged. Economic activity rebounded strongly in the second quarter of 2002, as exports were supported by stronger demand from the United States and final domestic demand grew sharply.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet